Effect of open and locked exercise on cognitive function in older adults - Yuping Zou (Quality in Sport)
Objective: The extension of life span and the decrease of fertility rate in the elderly population lead to the increasing aging proportion, and the natural growth of age is accompanied by aging. Cognitive diseases will emerge in large numbers at this stage, affecting the cognitive function of the elderly. Methods: The purpose of this review is to comprehensively explore the effects of open movement and locked exercise on cognitive function in the elderly. It discuss the specific effects and related neurobiological mechanisms of different types of exercise on cognitive function (including attention, memory, executive ability, etc.) in the elderly. Results: Open sports can effectively improve attention, executive function and cognitive flexibility in the elderly, and closed sports can have positive effects on memory and concentration by enhancing brain neuroplasticity and regulating neurotransmitters. Conclusion: although two types of movement on the cognitive function of the elderly has its emphasis, but overall, compared with closed movement, open movement in the elderly specific cognitive function (such as executive function, inhibitory control, task conversion, etc.) show more prominent effect, and help to reduce the brain caused by the age of atrophy and the risk of neurodegenerative changes.